Dams and agricultural lands affect energy sources and the trophic position of fish in a floodplain - Vinícius de Andrade Urbano; Driele Delanira-Santos; Matheus Maximilian Ratz Scoarize; Evanilde Benedito (Neotropical Ichthyology, 2024)
Abstract Landscape change caused by hydropower dam construction and invasion of agriculture in the riparian zone has been a catalyst for alterations in fish food web dynamics. The objectives of this study were to investigate the trophic state and land use of three rivers, one directly impacted by a dam; the trophic structure of four fish species of four trophic guilds; and the relationship between the trophic state and land use with trophic structure. We found a greater total allochthonous contribution in the dam-regulated river in contrast to its tributaries, along with less natural cover in the riparian zone, but a high percentage of natural vegetation on the islands. Additionally, we observed greater contribution of the riverine sources for all three rivers, independent of the trophic state and natural cover of the river. The trophic position was greater for the fish in the river in a protected area and lower in the rivers with a high percentage of agropastoral activities in the riparian areas. These findings show the importance of the conservation of the riverine zones mainly in dam-regulated rivers, because this vegetation provides the main energy source by fish.